Pengaruh Work-Life Balance terhadap Job Perfomance yang Dimediasi oleh Psychological Well-Being Pada Perawat - Jaelani, Ahmad Sandi; Nugraha, Yus (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
This study aims to look at the role of Psychological well-being as a variable mediating the relationship between Work-life balance and Job Performance in nurses in hospital group X. The method used in this study uses correlational quantitative with hypothesis analysis using Process by Andrew Hayes. The results showed a direct relationship between Work-life balance and Job Performance of 0.732 with a P value <0.05. Meanwhile, the indirect estimate value between Work-life balance and Job Performance is Mediation of Psychological Wel-Being of 0.419 with a P value <0.05 which means that Psychological well-being mediates the relationship between Work-life balance and Job Performance. The implications of the research findings indicate the necessity for policies and programs that support nurses' well-being to achieve a balance between professional and personal life. Initiatives aimed at enhancing psychological well-being, such as flexible work schedules and access to mental health resources, can not only improve job performance but also the quality of patient care, leading to a more resilient and efficient healthcare system.